THE IMPORTANCE AND NECESSITY OF STRATEGIC MANAGEMENT IN JOINT-STOCK COMPANIES - Ermatov Tokhir Sharipdjanovich (American Journals, 2025)
This article examines the importance and necessity of implementing effective strategic management practices in joint-stock companies to ensure sustainable growth, improve corporate governance, and enhance long-term competitiveness in the global market. The research emphasizes how strategic decision-making influences financial performance, shareholder value, and organizational adaptability in a dynamic economic environment. Additionally, it explores global trends and national approaches to strategic management, comparing best practices in corporate strategy formulation and execution. The article highlights the relationship between strategic planning and company performance, with a focus on aligning business goals with market opportunities and operational capabilities. Empirical analysis is presented to demonstrate how joint-stock companies that employ structured strategic management processes are more likely to attract investment, optimize resource allocation, and maintain resilience in times of economic uncertainty.
Keywords: Joint-stock companies, strategic management, corporate strategy, shareholder, external market, long-term investment, international markets.